(untitled) (Scientific journal of the Fergana State University, 2024)
Jack London’s exploration of the psychological impact of societal norms on characters’ development is a recurring theme in his works. London delves into the complex dynamics of how individuals internalize and wrestle with the expectations imposed upon them by society, offering readers a nuanced analysis of the internal conflicts and struggles that arise from the pressures of conforming to or defying societal norms. In addition, London’s works include social distinctions, human interactions with nature, and the problems of the community system with humans and nature. Through his novels, more insights have been obtained into the development of the community system, human relationships with nature, and the unaltered characteristics of humanity. In Jack London’s novels, the influence of social expectations on character development is enormous, and his works place great emphasis on social problems, the role of humanity in society, and the mesele of man in relation to nature. The esers of London show how people find, change and develop their place in the community system. His best-known works, such as "Call of the Wild" and "White Fang", " are about the animal world, but within them human and animal relations, the inherent attitude of man to nature, encounter the connections of the community system between humans and animals. Through these works, London focuses on the transformation of social expectations in nature, the development of the community system through human and animal relations.